Investigating factors associated with mother-daughter communication intentions about STD risks and condom use behaviour of female college students. (6th May 2021) - Salazar, Leslie Ramos; Khandelwal, Priyanka; Castillo, Yvette
Mothers play a significant role in influencing and educating their daughters about safe sexual practices. Given that college students are a high-risk population for contracting Sexually Transmitted Diseases (STDs) this study investigated the concepts of the Risk Perception Attitude (RPA) framework and their associations to help understand mothers' communication intentions and efficacy to communicating with their young adult daughters about STD risks and condom use. More specifically, this study investigated the relationships between mothers' perceived risk (severity and susceptibility) of their daughters contracting an STD, and how their self-efficacy was associated with mothers' intentions of communicating with their daughters about condom use to prevent STDs. This study found evidence that mothers' self-efficacy (over perceived daughter risks) had the highest association with mothers' communicative intentions and efficacy to communicate to daughters to prevent STDs. The study also discusses ideas for future mother-daughter sexual risk communication research to prevent STDs in college women.